From Columbine to Suzano: a socio-historical analysis of school shootings - Brasileiro, Juliana Montenegro [UNESP]; dos Santos, Larissa Medeiros Marinho; da Silva, Nilma Renildes [UNESP] (FapUNIFESP (SciELO), 2024)
Despite the eleven school shootings registered in Brazil, academic debate on the subject is still scarce. This essay sought to identify the historical-social categories that inform the offenders’ singularity. We consulted media materials about the Brazilian shootings and the categories found in the international literature. Based on a Marxist analysis, we highlight the social, historical and material conditions of the attacks. Male socialization, association with far-right groups and reproduced structural violence emerge as fundamental historical-social configurations. Moreover, job precarization and the assimilation of the neoliberal individual aggravate the split between collective and private dimensions, producing subjects that use market competitiveness as a measure for other relations. The precarization of public school makes it a target of attacks due to the break it establishes between the subject, education and work.
De Columbine a Suzano: un análisis sociohistórico de los ataques a escuelas
De Columbine à Suzano: une analyse socio-historique des attentats scolaires
Keywords: escola; escuela; materialism; materialismo; matérialisme; school; violence; violencia; violência; école